Mandailing Traditional Marriage Culture Acculturation in Medan City - Isra’ Pasu Mutiara; Desy Maya Sari; Rahimah; Nursukma Suri (al-Afkar, Journal For Islamic Studies, 2024)
This research seeks to see how urban identity influences the culture of the Mandailing ethnic community, especially through marriage customs which have experienced cultural acculturation with other ethnic cultures in the city of Medan. The method used in this research is a descriptive qualitative method with data collection techniques through literature study by examining related sources. The results found several forms of cultural acculturation to customs 1) Mandailing marriage, namely: acculturation to Islamic culture; 2) use of Henna/Mahendi on the bride; 3) Mardandang (Cooking) culture becomes Catering and Rijsttafel. All of these forms of acculturation are a form of group self-defense to maintain their ethnic existence, so they must adapt to the multicultural urban environment.